Accuracy of CT Perfusion–Based Core Estimation of Follow-up Infarction: Effects of Time Since Last Known Well. (24th May 2022) - Sarraj, Amrou; Campbell, Bruce C.V.; Christensen, Soren; Sitton, Clark W.; Khanpara, Shekhar; Riascos, Roy F.; Pujara, Deep; Shaker, Faris; Sharma, Gagan; Lansberg, Maarten G.; Albers, Gregory W.; ,
Abstract : Background and Objectives: To assess the accuracy of baseline CT perfusion (CTP) ischemic core estimates. Methods: From SELECT (Optimizing Patient Selection for Endovascular Treatment in Acute Ischemic Stroke), a prospective multicenter cohort study of imaging selection, patients undergoing endovascular thrombectomy who achieved complete reperfusion (modified Thrombolysis In Cerebral Ischemia score 3) and had follow-up diffusion-weighted imaging (DWI) available were evaluated. Follow-up DWI lesions were coregistered to baseline CTP. The difference between baseline CTP core (relative cerebral blood flow [rCBF] <30%) volume and follow-up infarct volume was classified as overestimation (core ≥10 mL larger than infarct), adequate, or underestimation (core ≥25 mL smaller than infarct) and spatial overlap was evaluated. Results: Of 101 included patients, median time from last known well (LKW) to imaging acquisition was 138 (82–244) minutes. The median baseline ischemic core estimate was 9 (0–31.9) mL and median follow-up infarct volume was 18.4 (5.3–68.7) mL. All 6/101 (6%) patients with overestimation of the subsequent infarct volume were imaged within 90 minutes of LKW and achieved rapid reperfusion (within 120 minutes of CTP). Using rCBF <20% threshold to estimate ischemic core in patients presenting within 90 minutes eliminated overestimation. Volumetric correlation between the ischemic core estimate and follow-up imaging improved as LKW time to imaging acquisition increased: Spearman ρ <90 minutes 0.33 ( p = 0.049), 90–270 minutes 0.63 ( p < 0.0001), >270 minutes 0.86 ( p < 0.0001). Assessment of the spatial overlap between baseline CTP ischemic core lesion and follow-up infarct demonstrated that a median of 3.2 (0.0–9.0) mL of estimated core fell outside the subsequent infarct. These regions were predominantly in white matter. Discussion: Significant overestimation of irreversibly injured ischemic core volume was rare, was only observed in patients who presented within 90 minutes of LKW and achieved reperfusion within 120 minutes of CTP acquisition, and occurred primarily in white matter. Use of a more conservative (rCBF <20%) threshold for estimating ischemic core in patients presenting within 90 minutes eliminated all significant overestimation cases. Trial Registration Information: ClinicalTrials.gov: NCT03876457.